The Relationship between Children Behavioral Disorders with Parenting Styles and Attachment Styles - Shirin Tarkeshdooz; Pegah Farokhzad (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objectives: Many researchers believe that behavioral disorder which a common and disabling disorder for families is the environment and children. This study aimed to investigate the relationship between children behavioral disorders with parenting styles and attachment styles. Material and Methods: The study was correlational. The study population included all girls and boys students with behavioral problems in third to fith grades of primary school in Tehran, regions 1 and 2 to the number 47137 in the 2015-16 school year. Using cluster sampling, 252 samples were selected. The data was completed by the mothers of the students. Pearson correlation coeffiient and regression analysis were used. Results: Results showed behavioral disorders signifiant positive correlation with the authoritarian parenting style (P<0.01) and permissive parenting style (P<0.01). Authoritative parenting style was not signifiantly correlated with behavioral disorders. As well as behavioral disorders have a negative correlation with secure attachment style (P<0.05) and ambivalent attachment style/ anxiety (P<0.01). The predictive role of attachment styles and parenting styles on behavioral disorders suggests that this model explained 12 percent of variance. Attachment styles and parenting styles were signifiant predictors (P<0.01). Conclusion: This study showed that there is a correlation between behavioral disorders and authoritarian and permissive parenting styles, but there was not a correlation between authoritative parenting style and behavioral disorders. The results of this study can help child psychologists to further understand the role of parenting style and parental involvement and appropriate intervention, taking into account the children's behavioral disorders.